Analisis Penggunaan Aplikasi "yesHeis" Dalam Penginjilan Pribadi - Steaven Octavianus (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat)
Steaven Octavianus, Analysis of Use of "yesHeis" Applications In Personal Evangelism. The globalization era and the advancement of science and technology as well as the internet made great impact to human life. This advancement also has an impact on the Christian evangelical life. In carrying out the Great Commission of the Lord Jesus, Christians can use this opportunity. However, this should still be managed and supervised wisely. This study will look at the use of the "yesHeis" app in sharing videos on social media Facebook and the responses of Christians about the app. This research will use qualitative approach with descriptive analysis method. Based on this research many people give positive response on this application. Even though many people positively respond to this app they are still hesitant to share it and even install it on their smart phone.